Proyecto de factibilidad de la creación de una empresa elaboradora de camotes al horno en forma de snack light en Guayaquil - Pagalo Manobanda, Jacqueline Del Carmen (2010)
The objective of this project is to analyze the feasibility of creating a processing firm baked potatoes in the form of light snack in Guayaquil, as a nutritious and low in calories from fat, because the traditional snacks do not offer the properties our product provides nutritional support, now this is the potato tuber has not been used in a process of industrial transformation, largely because there is a marked lack of information related to their functional benefits while contributing to the spread and agribusiness expansion in Ecuador. We will create loyalty in consumers, giving a product of good taste and quality. Developed a marketing plan for greater market share. To determine the feasibility of the project was necessary to conduct a financial analysis, covering all the components that the cash flow required for their implementation, for example, the costs and benefits of each period, projecting through year 10, then, measure these flows based on the Internal Rate of Return and Net Present Value calculation. Finally we conclude with the sensitivity analysis of the project.